23. Effect of Temu Kunci’s Root (Boesenbergia pandurata) Extract to Pseudomonas aeruginosa - Florentina Magdalena Girsang; T. Armansyah; Mahdi Abrar; Erina Erina; Darniati Darniati; Nuzul Asmilia (Jurnal Medika Veterinaria, 2019)
This study aimed to determine the effect of temu kunci’s extract (Boesenbergia pandurata) on the growth of Pseudomonas aeruginosa in vitro. This research was conducted using seven treatments with three replications. The experiment was carried out using Kirby Bauer’s method, the number of bacteria used was in accordance with the standards of Mc Farland 1. Blank discs were soaked in temu kunci’s extract in concentration of 10, 20, 30, 40, and 50%. Streptomycin was used as a positive control and sterile aquades as a negative control. All the discs were placed on the surface of bacteria cultured on MHA and incubated for 24 hours at 37 °C. Diameter of inhibition zone formed was measured by using a caliper. Data were analyzed descriptively. The average diameter of inhibition zone of temu kunci’s extract with a concentration of 10, 20, 30, 40 and 50% were 8.00, 12.30, 13.85, 19.16, and 19.86 mm, respectively. The average diameter of inhibition zone formed on the positive control and negative control were 14,25 and 0 mm, respectively. The conclusion showed that the temu kunci’s extract (Boesenbergia pandurata) has the ability to inhibit the growth of Pseudomonas aeruginosa.